Etnološka recepcija starovercev - Kozorog, Miha (Etnolog. Nova vrsta (Ljubljana), 2020)
Experts and the general public were recently surprised by Pavle Medvešček's discovery that a few decades ago a secret community of "Ancient Faith" believers was still living in Posočje. Four ethnologists reinterpreted Medvešček's material in the light of their own expert knowledge and gave it the legitimacy of an ethnographic source. A comparison of Medvešček's ethnological material and older material shows an important difference in the representations of the culture in question: whereas in the older material there are indications of heterogeneous traditions merging and of a hybrid cultural form, Medvešček reports about ordered and complete cultural wholes. The latter is actually very unusual in ethnology, which is why Medvešček's material may raise doubts as an ethnographic source.
Keywords: etnologija; Slovenci; staroverstvo; verovanje